EVALUATION OF THE THROMBOGENICITY OF THE VASCULAR ENDOTHELIUM IN PATIENTS IN THE ACUTE PHASE OF THE ISCHEMIC STROKE - E.V. MIKHAYLOV; I.N. PASECHNIK; O.P. BARANOVSKAYA; G.S GRIVKO (Паёми Сино)
Objective: To assess the thrombogenicity of the vascular endothelium based on laboratory parameters in patients in the acute phase of the ischemic stroke (IS), depending on the subtype of IS.